2020
DOI: 10.1038/s41418-020-0556-6
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the PIDDosome and caspase-2 as regulators of organogenesis and cellular differentiation

Abstract: The PIDDosome is a multiprotein complex that drives activation of caspase-2, an endopeptidase originally implicated in apoptosis. Yet, unlike other caspases involved in cell death and inflammation, caspase-2 seems to exert additional versatile functions unrelated to cell death. These emerging roles range from control of transcription factor activity to ploidy surveillance. Thus, caspase-2 and the PIDDosome act as a critical regulatory unit controlling cellular differentiation processes during organogenesis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 103 publications
(171 reference statements)
0
15
0
Order By: Relevance
“…Several reports implicate caspase-2 in neuronal cell death caused by NGF or beta-amyloids 8,14 . Whether these effects of caspase-2 require PIDDosome formation remains less clear 15 . Caspase-2 can also process tau protein leading to its accumulation in dendritic spines, which have been found to be increased in cognitively impaired mice and humans 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Several reports implicate caspase-2 in neuronal cell death caused by NGF or beta-amyloids 8,14 . Whether these effects of caspase-2 require PIDDosome formation remains less clear 15 . Caspase-2 can also process tau protein leading to its accumulation in dendritic spines, which have been found to be increased in cognitively impaired mice and humans 16 .…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Caspase-2 is also recruited to a large multiprotein complex called the PIDDosome 28 (see below). Caspase-2 is the only caspase with a classical nuclear localization signal that mediates its predominant localization to the nucleus 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that some have potential in developing drugs aimed at preventing osteoporosis, fatty liver diseases, or neurodegenerative disease. [60][61][62] Ding et al [47] have synthesized a fluorescent bioprobe containing two peptides, caspase-specific Asp-Glu-Val-Asp (Ac-DEVD) and cRGD, onto TPS units. While the fluorescence intensity of this probe remarkably increased in the presence of caspase-3, however, the probe was not emissive in aqueous solutions.…”
Section: Caspasesmentioning
confidence: 99%
“…Recent research has demonstrated that some have potential in developing drugs aimed at preventing osteoporosis, fatty liver diseases, or neurodegenerative disease. [ 60–62 ] Ding et al . [ 47 ] have synthesized a fluorescent bioprobe containing two peptides, caspase‐specific Asp‐Glu‐Val‐Asp (Ac‐DEVD) and cRGD, onto TPS units.…”
Section: Detection Of Miscellaneous Proteins Via Aie‐promoted Protein...mentioning
confidence: 99%